Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This paper estimated the output gap in Lithuania using three different methodologies-an HP filter, a panel regression, and a production function. This study examines how the levels of the current account deficit and the real exchange rate in Lithuania compare with estimates of their equilibrium values. The regression-based estimates are sensitive to the regression specifications and samples that determine equilibrium values. The large current account deficit in Lithuania may well be the equilibrium outcome of rapid income catch-up driven by strong fundamentals, including EU accession.